A highly efficient composite steel dust and mud washing solution treatment agent

By using efficient composite treatment agents in the steel dust, sludge and water elution chlorine process, the problem of lengthy process and inability to effectively remove thallium ions in traditional processes is solved, and the effect of efficient removal of heavy metal ions is achieved.

CN119191515BActive Publication Date: 2025-03-04中科博一环保科技有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411708871.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The traditional steel dust sludge water chlorine filtration process has problems such as large investment, long production process, numerous process control points, large wastewater treatment volume and inability to effectively remove thallium ions during the purification process.

Method used

A highly efficient composite steel dust sludge washing solution is used to treat the drug, including sodium hydroxide, sodium carbonate, potassium ferrate and chitosan-coated calcium peroxide-loaded tourmaline. By adjusting the pH value and the action of the flocculant, the efficient removal of heavy metal ions is achieved.

Benefits of technology

This treatment agent can effectively remove heavy metal ions and other impurity ions in the steel dust and sludge washing solution while shortening the process flow, significantly improve the processing efficiency, and effectively remove thallium ions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a highly efficient composite steel dust and mud washing solution treatment agent, belonging to the technical field of wastewater treatment. The treatment agent raw materials provided by the present invention include: 30-60 parts of sodium hydroxide, 30-60 parts of sodium carbonate, 0.45-0.9 parts of potassium ferrate and 12-16 parts of chitosan-coated loaded calcium peroxide tourmaline. The chitosan-coated loaded calcium peroxide tourmaline is based on tourmaline powder, loaded with calcium peroxide, and coated with a gel solution formed by chitosan to obtain a chitosan film coating layer, which is added to the washing solution. Chitosan can ensure the dispersibility of the loaded calcium peroxide tourmaline while adsorbing heavy metal ions. Calcium peroxide reacts with water, promotes the oxidation of heavy metals on the one hand, forms hydroxide precipitation, and locally releases heat on the other hand to produce a self-polarization effect of tourmaline, further improving adsorption performance. The purification treatment of the washing solution is realized under the synergistic effect of the multiple components of the treatment agent, simplifying the process flow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a high-efficiency composite steel dust and mud water washing solution treatment agent. Background Art

[0002] The steel industry is a typical energy and resource-intensive industry. Steel production consumes a lot of energy and resources, and produces a lot of industrial solid waste. If the solid waste is not properly handled, it will not only bring huge pressure to the regional ecological environment, but also cause a huge waste of resources.

[0003] Steel dust sludge originates from steel production workshops. It generally refers to waste generated after dust removal facilities are used to remove dust from high-temperature flue gas during production processes such as raw material processing, sintering, pelletizing, ironmaking, and steelmaking, as well as waste generated in subsequent processing links and cleaning processes. Most of the potassium and sodium in steel dust sludge exist in the form of chlorides. The wet dechlorination process, that is, multi-stage water washing, can reduce the sodium, potassium, and chlorine content. The washed filter cake can be recycled through a pyrometallurgical process. The washed filtrate can be purified (removing weight, hardness, and thallium, etc.) and then evaporated to extract salt to produce industrial products such as sodium chloride and potassium chloride, realizing the comprehensive recovery of potassium, sodium, chlorine and other resources.

[0004] The heavy metal impurity elements in the water-washed dechlorination filtrate of steel dust are mainly Fe, Zn, Pb, Cd, Ca, Mg, Tl, etc. Failure to purify the filtrate will affect the normal operation of the subsequent evaporation system and the quality of the potassium and sodium salt products. The purification process in the traditional process usually adopts a step-by-step precipitation method, that is, by adjusting the pH of the solution system, Pb, Zn, Fe, Ca, and Mg meet the precipitation conditions in turn, so as to achieve the purpose of step-by-step removal of the corresponding ions. During the treatment process, this process requires repeated process operations such as filter pressing, slag washing, and pulping. It has the disadvantages of large investment, lengthy production process, numerous process control points, and large wastewater treatment volume, and it cannot effectively remove thallium ions. Summary of the invention

[0005] The object of the present invention is to provide a highly efficient composite steel dust and mud water washing solution treatment agent, which can efficiently remove impurities while shortening the process flow and improving the treatment efficiency.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The present invention provides a high-efficiency composite steel dust and mud water washing solution treatment agent, which comprises the following raw materials in parts by weight:

[0008] 30-60 parts of sodium hydroxide, 30-60 parts of sodium carbonate, 0.45-0.9 parts of potassium ferrate and 12-16 parts of chitosan-coated calcium peroxide-loaded tourmaline.

[0009] Sodium hydroxide adjusts the pH to make the metal ion Zn 2+ , Fe 2+ , Pb 2+ 、Cd 2+ Sodium carbonate forms a hydroxide precipitate, which makes the Ca in the solution 2+ Mg 2+ Ions generate CaCO3 and MgCO3 precipitation. Potassium ferrate can make TI + Ion oxidation to TI 3+ ions, generating TI(OH)3 precipitate.

[0010] The chitosan coating layer in the chitosan-coated calcium peroxide-loaded tourmaline can prevent calcium peroxide from decomposing in contact with moist air. After being put into water, the chitosan coating layer swells when it meets water and then falls off under stirring, gradually leaking out calcium peroxide and tourmaline. Calcium peroxide and water slowly react to produce calcium hydroxide and oxygen. Oxygen can promote the oxidation reaction. The heat released by the reaction can cause the local temperature of the tourmaline to change, triggering a spontaneous polarization effect. Under the synergistic effect of the surface adsorption effect, heavy metal ions can be adsorbed, and the local heavy metal ion concentration increases, among which TI + Increased concentration can promote TI on the tourmaline surface + Oxidation to TI 3 + , and then form hydroxide precipitation. In addition, chitosan can simultaneously adsorb heavy metal ions and improve the removal rate of heavy metal ions.

[0011] Furthermore, the preparation steps of the chitosan-coated calcium peroxide-loaded tourmaline are as follows:

[0012] S1. Dissolve tourmaline powder and calcium chloride in deionized water and disperse them by ultrasonic for 20 minutes to obtain a dispersion;

[0013] S2, placing the dispersion in an ice bath at 0°C, adding ammonia water to the dispersion while stirring, adding hydrogen peroxide dropwise while continuing to stir, allowing the dispersion to react for 20 minutes after the addition is complete, filtering and washing after the reaction is complete, and drying at 90°C for 3 hours to obtain calcium peroxide-loaded tourmaline;

[0014] S3. Dissolve chitosan in an aqueous solution of acetic acid with a mass fraction of 1% to form a gel solution, quickly stir and mix the loaded calcium peroxide tourmaline and the gel solution to obtain a mixture, place the mixture in an aqueous solution of sodium hydroxide with a mass fraction of 30% for 10 minutes to form a gel layer, and dry at 60°C to obtain chitosan-coated loaded calcium peroxide tourmaline.

[0015] Furthermore, the particle size of the tourmaline powder is 0.5-1 μm;

[0016] The mass ratio of the tourmaline powder to calcium chloride is 10:1-5.

[0017] Furthermore, the solid-liquid ratio of the dispersion is 1:2.

[0018] Furthermore, the mass fraction of the ammonia water is 25%, and the volume ratio of the ammonia water to the dispersion is 1:2.

[0019] Furthermore, the mass fraction of the hydrogen peroxide is 30%, the volume ratio of the hydrogen peroxide to the dispersion is 1-1.5:1, and the dropping time of the hydrogen peroxide is 8 minutes.

[0020] Furthermore, the mass proportion of chitosan in the gel solution is 2%.

[0021] Furthermore, the mass ratio of the loaded calcium peroxide tourmaline to the gel liquid is 20-30:1.

[0022] Furthermore, the thickness of the chitosan coating layer in the chitosan-coated calcium peroxide-loaded tourmaline is 0.05-0.08 mm.

[0023] Furthermore, the method of using the treatment agent is as follows:

[0024] Add the treatment agent to the steel dust sludge washing solution, adjust the pH range of the solution to 9-11, add the organic flocculant polyacrylamide after stirring for 10-30 minutes, the dosage of polyacrylamide is 0.03% of the solution volume, stir at a low speed of 20r / min for 30 minutes, and separate the solid and liquid after static precipitation.

[0025] The role of polyacrylamide is to adsorb small flocs in the solution into large flocs to accelerate sedimentation, and through the "sweeping" effect of the large flocs during sedimentation, the treatment effect of other ions is improved.

[0026] Beneficial effects of the present invention:

[0027] (1) By controlling the proportion of each component in the treatment agent, the heavy metal ions and other impurity ions can be removed efficiently. The sodium hydroxide and sodium carbonate in the treatment agent work together to precipitate the metal ions in the solution, and potassium ferrate is used to oxidize thallium to form hydroxide precipitation under alkaline conditions. Chitosan-coated calcium peroxide-loaded tourmaline promotes the precipitation of heavy metal ions through the synergistic effect of chitosan, calcium peroxide and tourmaline.

[0028] (2) The treatment agent of the present invention can remove heavy metal ions and other impurity ions in the steel dust sludge washing solution at one time. Compared with the traditional step-by-step precipitation method of removing heavy metals and impurities, it can reduce the number of slag-liquid separation and slag washing, greatly shorten the process flow, and reduce equipment investment. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] Preparation of chitosan-coated calcium peroxide-loaded tourmaline:

[0032] S1. Dissolve tourmaline powder (particle size 0.5-1 μm) and calcium chloride in deionized water, the mass ratio of tourmaline powder to calcium chloride is 10:1, and disperse by ultrasonic for 20 minutes to obtain a dispersion with a solid-liquid ratio of 1:2;

[0033] S2. Place the dispersion in an ice bath at 0°C, add ammonia water (mass fraction of 25%) to the dispersion while stirring, the volume ratio of ammonia water to the dispersion is 1:2, continue to stir and drop hydrogen peroxide (mass fraction of 30%), the volume ratio of hydrogen peroxide to the dispersion is 1:1, the dropping time is 8 minutes, after the dropwise addition is completed, let it stand for 20 minutes to react, after the reaction is completed, filter and wash, and dry at 90°C for 3 hours to obtain the calcium peroxide loaded tourmaline;

[0034] S3. Dissolve chitosan in an acetic acid aqueous solution with a mass fraction of 1% to form a gel solution, in which the mass proportion of chitosan in the gel solution is 2%. The calcium peroxide-loaded tourmaline and the gel solution are quickly stirred and mixed at a mass ratio of 20:1 to obtain a mixture, which is placed in a sodium hydroxide aqueous solution with a mass fraction of 30% for 10 minutes to form a gel layer, and the mass ratio of the mixture to the sodium hydroxide aqueous solution is 1:100. After drying at 60°C, chitosan-coated calcium peroxide-loaded tourmaline is obtained, and the thickness of the chitosan coating layer is 0.05-0.06mm.

[0035] Example 2

[0036] Preparation of chitosan-coated calcium peroxide-loaded tourmaline:

[0037] S1. Dissolve tourmaline powder (particle size 0.5-1 μm) and calcium chloride in deionized water, the mass ratio of tourmaline powder to calcium chloride is 10:3, and disperse by ultrasonic for 20 minutes to obtain a dispersion with a solid-liquid ratio of 1:2;

[0038] S2. Place the dispersion in an ice bath at 0°C, add ammonia water (mass fraction of 25%) to the dispersion while stirring, the volume ratio of ammonia water to the dispersion is 1:2, continue stirring and dropwise add hydrogen peroxide (mass fraction of 30%), the volume ratio of hydrogen peroxide to the dispersion is 1.2:1, the dropping time is 8 minutes, after the dropwise addition is completed, let it stand for 20 minutes to react, after the reaction is completed, filter and wash, and dry at 90°C for 3 hours to obtain the calcium peroxide loaded tourmaline;

[0039] S3. Dissolve chitosan in an acetic acid aqueous solution with a mass fraction of 1% to form a gel solution, in which the mass proportion of chitosan in the gel solution is 2%. The calcium peroxide-loaded tourmaline and the gel solution are quickly stirred and mixed at a mass ratio of 25:1 to obtain a mixture, which is placed in a sodium hydroxide aqueous solution with a mass fraction of 30% for 10 minutes to form a gel layer, and the mass ratio of the mixture to the sodium hydroxide aqueous solution is 1:100. After drying at 60°C, chitosan-coated calcium peroxide-loaded tourmaline is obtained, and the thickness of the chitosan coating layer is 0.06-0.07mm.

[0040] Example 3

[0041] Preparation of chitosan-coated calcium peroxide-loaded tourmaline:

[0042] S1. Dissolve tourmaline powder (particle size 0.5-1 μm) and calcium chloride in deionized water, the mass ratio of tourmaline powder to calcium chloride is 10:5, and disperse by ultrasonic for 20 minutes to obtain a dispersion with a solid-liquid ratio of 1:2;

[0043] S2. Place the dispersion in an ice bath at 0°C, add ammonia water (mass fraction of 25%) to the dispersion while stirring, the volume ratio of ammonia water to the dispersion is 1:2, continue stirring and dropwise add hydrogen peroxide (mass fraction of 30%), the volume ratio of hydrogen peroxide to the dispersion is 1.5:1, the dropping time is 8 minutes, after the dropwise addition is completed, let it stand for 20 minutes to react, after the reaction is completed, filter and wash, and dry at 90°C for 3 hours to obtain the loaded calcium peroxide tourmaline;

[0044] S3. Dissolve chitosan in an acetic acid aqueous solution with a mass fraction of 1% to form a gel solution, in which the mass proportion of chitosan in the gel solution is 2%. The calcium peroxide-loaded tourmaline and the gel solution are quickly stirred and mixed at a mass ratio of 30:1 to obtain a mixture, which is placed in a sodium hydroxide aqueous solution with a mass fraction of 30% for 10 minutes to form a gel layer, and the mass ratio of the mixture to the sodium hydroxide aqueous solution is 1:100. After drying at 60°C, chitosan-coated calcium peroxide-loaded tourmaline is obtained, and the thickness of the chitosan coating layer is 0.07-0.08mm.

[0045] Example 4

[0046] This embodiment provides an effective composite steel dust and mud water washing solution treatment agent, which includes the following raw materials in parts by weight:

[0047] 30 parts of sodium hydroxide, 30 parts of sodium carbonate, 0.45 parts of potassium ferrate, and 12 parts of chitosan-coated calcium peroxide-loaded tourmaline, where the chitosan-coated calcium peroxide-loaded tourmaline is prepared in Example 1.

[0048] The treatment agent was added into the steel dust sludge washing solution. The pH value of the solution was adjusted to 9 by the treatment agent. After stirring for 30 minutes, the organic flocculant polyacrylamide was added. The dosage of polyacrylamide was 0.03% of the solution volume. The solution was stirred at a low speed of 20 r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0049] Example 5

[0050] The difference from Example 4 is that the chitosan-coated calcium peroxide-loaded tourmaline prepared in Example 2 is used.

[0051] Example 6

[0052] The difference from Example 4 is that the chitosan-coated calcium peroxide-loaded tourmaline prepared in Example 3 is used.

[0053] Example 7

[0054] This embodiment provides an effective composite steel dust and mud water washing solution treatment agent, which includes the following raw materials in parts by weight:

[0055] 60 parts of sodium hydroxide, 40 parts of sodium carbonate, 0.75 parts of potassium ferrate, and 12 parts of chitosan-coated calcium peroxide-loaded tourmaline, where the chitosan-coated calcium peroxide-loaded tourmaline is prepared in Example 2.

[0056] The treatment agent was added into the steel dust sludge washing solution. The pH value of the solution was adjusted to 11 by the treatment agent. After stirring for 30 minutes, the organic flocculant polyacrylamide was added. The dosage of polyacrylamide was 0.03% of the solution volume. The solution was stirred at a low speed of 20 r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0057] Example 8

[0058] This embodiment provides an effective composite steel dust and mud water washing solution treatment agent, which includes the following raw materials in parts by weight:

[0059] 50 parts of sodium hydroxide, 60 parts of sodium carbonate, 0.9 parts of potassium ferrate, and 12 parts of chitosan-coated calcium peroxide-loaded tourmaline, where the chitosan-coated calcium peroxide-loaded tourmaline is prepared in Example 2.

[0060] The treatment agent was added into the steel dust sludge washing solution. The pH value of the solution was adjusted to 10.5 by the treatment agent. After stirring for 30 minutes, the organic flocculant polyacrylamide was added. The dosage of polyacrylamide was 0.03% of the solution volume. The solution was stirred at a low speed of 20 r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0061] Example 9

[0062] This embodiment provides an effective composite steel dust and mud water washing solution treatment agent, which includes the following raw materials in parts by weight:

[0063] 50 parts of sodium hydroxide, 60 parts of sodium carbonate, 0.9 parts of potassium ferrate, and 14 parts of chitosan-coated calcium peroxide-loaded tourmaline, where the chitosan-coated calcium peroxide-loaded tourmaline is prepared in Example 2.

[0064] The treatment agent was added into the steel dust sludge washing solution. The pH value of the solution was adjusted to 10.5 by the treatment agent. After stirring for 30 minutes, the organic flocculant polyacrylamide was added. The dosage of polyacrylamide was 0.03% of the solution volume. The solution was stirred at a low speed of 20 r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0065] Example 10

[0066] This embodiment provides an effective composite steel dust and mud water washing solution treatment agent, which includes the following raw materials in parts by weight:

[0067] 50 parts of sodium hydroxide, 60 parts of sodium carbonate, 0.9 parts of potassium ferrate, and 16 parts of chitosan-coated calcium peroxide-loaded tourmaline, where the chitosan-coated calcium peroxide-loaded tourmaline is prepared in Example 2.

[0068] The treatment agent was added into the steel dust sludge washing solution. The pH value of the solution was adjusted to 10.5 by the treatment agent. After stirring for 30 minutes, the organic flocculant polyacrylamide was added. The dosage of polyacrylamide was 0.03% of the solution volume. The solution was stirred at a low speed of 20 r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0069] Comparative Example 1

[0070] The difference between this comparative example and Example 10 is that different precipitants are used for step-by-step precipitation.

[0071] Sodium hydroxide was added to the steel dust and mud washing solution to adjust the pH to 10.0. After stirring for 30 minutes, the reaction formed a precipitate. After standing, the precipitate was removed to obtain a supernatant. Sodium carbonate was added to the supernatant. The amount of sodium carbonate added was 1.2 times the total hardness of the solution. After precipitation treatment, a supernatant was obtained. Hydrogen peroxide (mass fraction 30%) and ferric sulfate were added to the supernatant. The ratio of the two was 200mL:1g. After precipitation treatment, an organic flocculant polyacrylamide was added to the supernatant. The dosage of polyacrylamide was 0.03% of the volume of the solution. The solution was stirred at a low speed of 20r / min for 30 minutes. After standing and settling, the solid and liquid were separated. The supernatant was taken for component detection.

[0072] The steel dust sludge washing solutions and the treated supernatant solutions of Examples 4 to 10 and Comparative Example 1 were sampled for component testing, and the results are shown in Table 1:

[0073] ;

[0074] As can be seen from Table 1, Examples 4 to 6 use chitosan-coated calcium peroxide-loaded tourmaline prepared by Examples 1 to 3. As the loading amount of calcium peroxide on the tourmaline increases, the effect of removing heavy metals and impurity ions is improved, but due to the limit of the loading amount, the improvement effect of Example 6 compared with Example 5 is not obvious. Based on the different element contents in the washing solution, Examples 5, 7 and 8 adjust the proportion of each component in the agent to maintain an excellent removal effect. Examples 9 and 10 increase the proportion of chitosan-coated calcium peroxide-loaded tourmaline on the basis of Example 8, and the removal rate of thallium is significantly increased. Comparative Example 1 uses different precipitants to treat the washing solution in steps, and Example 10 of the present invention has a significantly better purification effect than Comparative Example 1.

[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly efficient composite steel dust and mud washing solution treatment agent, characterized in that: The following raw materials are included by mass: 30-60 parts of sodium hydroxide, 30-60 parts of sodium carbonate, 0.45-0.9 parts of potassium ferrate and 12-16 parts of chitosan-coated calcium peroxide-loaded tourmaline; The preparation steps of the chitosan-coated calcium peroxide-loaded tourmaline are as follows: S1, dissolving tourmaline powder and calcium chloride in deionized water, and ultrasonically dispersing to obtain a dispersion; S2, placing the dispersion in an ice bath, adding ammonia water to the dispersion while stirring, adding hydrogen peroxide dropwise while continuing to stir, allowing to stand for reaction after the addition is complete, filtering after the reaction is complete, washing and drying to obtain calcium peroxide-loaded tourmaline; S3, dissolving chitosan in an acetic acid aqueous solution to form a gel solution, rapidly stirring and mixing the calcium peroxide loaded tourmaline and the gel solution to obtain a mixture, placing the mixture in a sodium hydroxide aqueous solution to form a gel layer, and drying to obtain the chitosan-coated calcium peroxide loaded tourmaline.

2. A highly efficient composite steel dust and mud washing solution treatment agent according to claim 1, characterized in that: The particle size of the tourmaline powder is 0.5-1 μm; The mass ratio of the tourmaline powder to calcium chloride is 10:1-5.

3. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1 is characterized in that: The solid-to-liquid ratio of the dispersion is 1:

2.

4. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1 is characterized in that: The mass fraction of the ammonia water is 25%, and the volume ratio of the ammonia water to the dispersion is 1:

2.

5. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1 is characterized in that: The mass fraction of the hydrogen peroxide is 30%, the volume ratio of the hydrogen peroxide to the dispersion is 1-1.5:1, and the dropping time of the hydrogen peroxide is 8 minutes.

6. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1 is characterized in that: The mass proportion of chitosan in the gel solution is 2%.

7. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1, characterized in that: The mass ratio of the loaded calcium peroxide tourmaline to the gel liquid is 20-30:

1.

8. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1 is characterized in that: The thickness of the chitosan coating layer in the chitosan-coated calcium peroxide-loaded tourmaline is 0.05-0.08 mm.

9. The high-efficiency composite steel dust and mud washing solution treatment agent according to claim 1, characterized in that: The method of using the treatment agent is as follows: Add the treatment agent to the steel dust sludge washing solution, adjust the pH range of the solution to 9-11, stir for 10-30 minutes, add the organic flocculant polyacrylamide, the dosage of polyacrylamide is 0.03% of the solution volume, stir for 30 minutes, let it stand and settle before solid-liquid separation.

Citation Information

Patent Citations

  • Sustained-release agent for in-situ remediation of chlorohydrocarbon-contaminated groundwater in deep mine

    CN110407266A